Testing for Contagion during the Asian Crisis - Kessara Thanyalakpark; Darren Filson (Claremont McKenna College, Department of Economics, 2001)
This paper uses a stationary multivariate asymmetric GARCH specification of the international capital asset pricing model to investigate contagion effects across six developed and emerging East Asian markets as well as the US and the World markets around the time of the Asian currency crisis of 1997. After controlling for domestic shocks and spillover effects, the results suggest that the region's equity markets volatility processes display interdependence but little contagion. The results indicate contagion effects only from Thailand to Korea.
Keywords: 330